The explanatory power of Carnegie Classification in predicting engagement indicators: a multilevel analysis - Gök, Enes; Aydin, Burak (Frontiers in Education, 2024)
The study aims to explore the effect of the type of higher education institution on students' engagement. The metaanalyses of multilevel regression coefficients revealed significant relationships between the type of higher education institution and student engagement indicators across the years from 2013 to 2019. Comparing different types of higher education institutions with the base category, our findings revealed significant differences in effective teaching practices, discussion with diverse others, and student-faculty interaction consistent throughout the years.These findings are expected to provide insights for institutional administrators, policymakers, and researchers given that student engagement in higher education has become an indicator of quality all around the world.